2020
DOI: 10.12659/ajcr.919956
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Rupture of a Huge Splenic Artery Aneurysm: A Case Report

Abstract: Objective:Unknown ethiology Background:Splenic artery aneurysm is uncommon in a healthy young male patient. With spontaneous rupture, it can quickly become life-threatening. Our aim is to highlight the possibility of splenic artery aneurysm among healthy young patients and its presentation as recurrent abdominal pain, while pending rupture is possible, which can present a diagnostic challenge. The rare occurrence and spontaneous rupture of a splenic artery aneurysm are often fatal outside an inpatient setting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Splenic artery aneurysms were first described in 1770 by Beaussier in autopsies. More than a hundred years passed before the first preoperative diagnosis was made, in 1920 by Hoegler, and it was only in 1940 that the first surgical intervention was described [ 4 , 6 ]. Around 80% of splenic artery aneurysms are asymptomatic and diagnosed incidentally during imaging studies [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Splenic artery aneurysms were first described in 1770 by Beaussier in autopsies. More than a hundred years passed before the first preoperative diagnosis was made, in 1920 by Hoegler, and it was only in 1940 that the first surgical intervention was described [ 4 , 6 ]. Around 80% of splenic artery aneurysms are asymptomatic and diagnosed incidentally during imaging studies [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Manifestations, if present, tend to be nonspeci c, often involving epigastric and left-upper quadrant abdominal pain [3].…”
Section: Case Presentationmentioning
confidence: 99%
“…Rupture, reported in 3 to 10% of all splenic aneurysms, can induce a dramatic hypotensive shock with a notable mortality rate [3]. Rupture risk correlates with factors such as aneurysm size, pregnancy, cirrhosis, and liver transplantation, with an aneurysm exceeding 2 cm in diameter considered predisposed to rupture [1].…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, before a definite pathological diagnosis is made, making a suspected diagnosis of ADHD based on clinical manifestations alone is challenging because common intestinal disorders can present with these similarly[ 9 ]. Although many studies have reported patients presenting to the ED with recurrent abdominal symptoms for a number of disorders[ 10 - 13 ], there are few data involving ADHD. It is hard for most ED doctors to associate common abdominal symptoms with ADHD specifically.…”
Section: Introductionmentioning
confidence: 99%